Geolocation-Based Mobile Application - Saeed, Shwan Hadi; Mustafa, Twana; Khoshnaw, Karwan; Shwany, Zardasht Abdulaziz (Igi Global, 2022)
Geolocation denotes the position of an object in a geographical context. The geolocation algorithm is characterized by four Ms: which Measurements are used, the Map, the Motion model used for describing the motion of the object, and the filtering Method. This paper describes a general framework for geolocation based on the particle filter, and Android Studio is used for design and programming. Also, Google Firebase is used as a database for save location and to display only the ones that are within one kilometer's radius from the user carnet location. In this app, when locations save or select or make filtering, the app describes a place and will show all information about the place that has been selected on the map. Several examples based on real data are used to illustrate various combinations of sensors and maps for geolocation. Finally, and aim of this paper is to investigate efficient ways to store geolocation in Google Firebase as a set of latitudes and longitudes based on mobile and web.
Keywords: Android Studio; API; Geolocation; Google Firebase; Latitude; Location; Longitude; Map; Mobile